2022
DOI: 10.3389/fmicb.2022.1040302
|View full text |Cite
|
Sign up to set email alerts
|

The secreted FoAPY1 peptidase promotes Fusarium oxysporum invasion

Abstract: The secretion of peptidases from several pathogens has been reported, but the biological function of these proteins in plant-pathogen interactions is poorly understood. Fusarium oxysporum, a soil-borne plant pathogenic fungus that causes Fusarium wilt in its host, can secrete proteins into host plant cells during the infection process to interfere with the host plant defense response and promote disease occurrence. In this study, we identified a peptidase, FoAPY1, that could be secreted from F. oxysporum depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…When pathogens infect and secrete effectors to host cells, the basal defense responses of plants, such as ROS bursts, resistance gene expression, and cell death, are activated to inhibit the pathogen growth and development ( Lyu et al, 2016 ; Kettles et al, 2018 ; Yang et al, 2018 ). In our study, transient expression of FolAsp protein in N. benthamiana did not induce cell death, similar to the recent findings of a peptidase effector FoAPY1 from Fol , which does not have the ability to induce cell death ( Qian et al, 2022b ). This family of aspartate proteases is also annotated by the MEROPS database as the peptidase family A1 (pepsin A, clan AA) ( Santos et al, 2013 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…When pathogens infect and secrete effectors to host cells, the basal defense responses of plants, such as ROS bursts, resistance gene expression, and cell death, are activated to inhibit the pathogen growth and development ( Lyu et al, 2016 ; Kettles et al, 2018 ; Yang et al, 2018 ). In our study, transient expression of FolAsp protein in N. benthamiana did not induce cell death, similar to the recent findings of a peptidase effector FoAPY1 from Fol , which does not have the ability to induce cell death ( Qian et al, 2022b ). This family of aspartate proteases is also annotated by the MEROPS database as the peptidase family A1 (pepsin A, clan AA) ( Santos et al, 2013 ).…”
Section: Discussionsupporting
confidence: 92%
“…We previously performed a secretome-wide analysis in Fol to provide new sight of infection-related proteins and found that most of them with an N-terminal SP were annotated as enzymes ( Li J. et al, 2020 ). To date, three secreted proteins are shown to contribute virulence, and two of them encode the ribonuclease and peptidase, respectively ( Li et al, 2022 ; Qian et al, 2022a , b ). In this study, we characterized one aspartic protease FolAsp from the Fol secretome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations